AQAD NIKAH PESPEKTIF FIQH DAN KOMPILASI HUKUM ISLAM - Muhazir Muhazir (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2019)
Regulations relating to private matters such as marriage and other civil matters are regulated in such a way as to achieve the objectives of the law itself. Therefore, howimportant is the position of law in the social order. Likewise in the concept of marriage, inorder to regulate and protect and protect human rights, it is necessary to make a formallegal codification in order to have legal power that can guarantee each individual.Especially in this marriage concerning private matters which are very urgent to protect, thisis due to factors arising from family problems, both concerning the protection of his wife,husband and children. Aqad marriage in marriage has an important role in determining thelegal or illegitimate marriage, because aqan is a binding bond both legally and morallybetween two individuals.